The Effect of Fermentation of High- or Low-Tannin Fava Bean on Glucose Tolerance, Body Weight, Cardiovascular Function, and Blood Parameters in Dogs After 7 Days of Feeding: Comparison With Commercial Diets With Normal vs. High Protein - Reis, Luciana G.; Morris, Tressa; Quilliam, Chloe; Rodrigues, Lucas A.; Loewen, Mathew E.; Weber, Lynn P. (Frontiers in Veterinary Science, 2021)
Fava bean, which is available in high and low-tannin varieties, is not an approved pet food ingredient and was not included in the ‘assumed to be safe’ category based on its ability to cause favism and hemolytic anemia in susceptible humans. The effects of 7-day feeding of test canine diets containing moderate protein (~27%) were compared to two control commercial diets with normal (NP, grain-containing, ~25% protein) or high protein (HP, grain-free, ~41% protein). Fava bean diets were formulated either with or without Candida. utilis fermentation processing to reduce antinutritional factors. Glucose tolerance, body weight, cardiovascular function, and blood parameters were investigated in beagles fed the NP or HP diets or a randomized, crossover, 2 × 2 Latin square design of the fava bean diets: unfermented high-tannin (UF-HT), fermented high-tannin (FM-HT), unfermented low-tannin (UF-LT) and fermented low-tannin (FM-LT). After 7 days, HP decreased red blood cells (RBC) (P < 0.05) compared to NP, while FM increased RBC compared to UF. HP increased blood bicarbonate, calcium, phosphorus, urea, cholesterol, and albumin:globulin ratio, while decreasing bilirubin, liver enzymes and total protein. Sodium:potassium ratio was increased in UF-HT, decreased in FM-HT, and intermediate in LT regardless of fermentation. Blood phosphorus was increased in HT. Blood amylase was increased in FM-HT, decreased in FM-LT, being intermediate in UF regardless of fava bean variety. Blood direct bilirubin was decreased in HT regardless of fermentation. Of note, left ventricular end-systolic volume and cardiac output were increased in NP compared to HP-fed dogs, but were normal and had no significant differences among the fava bean diets. As expected, plasma taurine, cystine, and cysteine levels were increased in HP- compared to NP-fed dogs. Plasma cysteine levels were increased in HT- compared to LT-fed dogs and in FM- compared to UF-fed dogs. Taken together, these results show that fava bean appears to be safe as a dog food ingredient at least in the short term, and its nutritional value appears improved by fermentation. Moreover, blood chemistry parameters and cardiovascular function were impacted by protein content which merits further investigation with longer term feeding trials.